Determinants of Functional Capacity and Quality of Life After Implantation of a Durable Left Ventricular Assist Device - Kiran K Mirza; Finn Gustafsson (Cardiac Failure Review)
Continuous-flow left ventricular assist devices (LVAD) are increasingly used as destination therapy in patients with end-stage heart failure and, with recent improvements in pump design, adverse event rates are decreasing. Implanted patients experience improved survival, quality of life (QoL) and functional capacity (FC). However, improvement in FC and QoL after implantation is not unequivocal, and this has implications for patient selection and preimplantation discussions with patients and relatives. This article identifies preimplantation predictors of lack of improvement in FC and QoL after continuous-flow LVAD implantation and discusses potential mechanisms, allowing for the identification of potential factors that can be modified. In particular, the pathophysiology behind insufficient improvement in peak oxygen uptake is discussed. Data are included from 40 studies, resulting in analysis of >700 exercise tests. Mean peak oxygen uptake was 13.4 ml/kg/min (equivalent to 48% of predicted value; 259 days after implantation, range 31–1,017 days) and mean 6-minute walk test distance was 370 m (182 days after implantation, range 43–543 days). Finally, the interplay between improvement in FC and QoL is discussed.